Efektivitas Aplikasi Media Pembelajaran Berbasis Augmented Reality pada Mata Pelajaran Geografi : (Studi Kasus Kelas X IPS SMA Negeri 2 Bungo) - Prayitno, Hari; Menrisal; Astri Indah Juwita (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effectiveness of making Android Learning Media Applications Based on Augmented Reality in Geography Subjects for Class X IPS at SMA Negeri 2 Bungo in the Academic Year 2022/2023. This study uses research development methods (research & development). The research subjects were 72 people. The research model used is the development research model (ADDIE), with the design development steps as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the overall effectiveness test assessment of the effectiveness of Augmented Reality-Based Android Learning Media in Geography Class X IPS at SMA Negeri 2 Bungo amounted to 88.06% so that the level of effectiveness can be interpreted to be very effective in use. In conclusion, based on the assessment along with expert input as well as the results of field trials of Augmented Reality-Based Android Learning Media as a learning medium, it has been tested for feasibility, superiority, and can be used in the learning process in Geography class X IPS at SMA Negeri 2 Bungo.